The Role of Stakeholders in Co-Management of Mangrove in The Economic Development of Coastal Villages on Madura Island - Wahyurini , Endang Tri (International Research & Development for Human Beings (IRDH), 2025)
Economic development in coastal areas still requires special attention and is very important to do. Various kinds of factors can affect the process of economic development of coastal villages. One of the potential natural resources that can be managed to improve the economy of coastal communities is mangroves, but until now mangroves have not become a priority so that the condition is increasingly depressed. Efforts to improve the economy of coastal communities can be carried out with proper and correct mangrove management through mangrove co- management. The research was conducted on the coastal of Madura Island. The purpose of this study is to analyze how the role of stakeholders and institutions towards mangrove co- management and economic development of coastal villages. Research methods with in-depth quantitative and qualitative. Analysis using SEM Warp-PLS. The results of the research analysis show that the role of stakeholders and institutions has a significant positive effect on mangrove co management and the economic development of coastal villages on Madura Island.